Perbandingan Komposisi Media Tanam Tanah Ultisol, Blotong dan Arang Sekam Terhadap Pertumbuhan Bibit Tebu (Saccaharum officinarum L.) Asal Bud Chips di Polybag - Situmorang, Leonardo Tamoko; Hayata, Hayata; Nasamsir, Nasamsir (Universitas Batanghari, 2024)
A planting media composition consisting of ultisol soil, composted sugar cane residue (blotong)and husk charcoal is needed to support the growth of sugarcane (Saccharum officinarum L.) seedlings from bud chips. The aim of this research was to determine the comparison of the planting media composition consisting of the ultisol, blotong and husk charcoal on the growth of sugar cane (Saccaharum officinarum L,.) seedlings from Bud Chips in Polybags. This research used a completely randomized design (CRD) with one treatment factor, i.e. the planting media composition consisting of ultisol, blotong and husk charcoal with the following volume ratio: V1 = (1 l) + (0.5 l) + (0.5 l), V2 = (0.5 l) + (0.5 l) + (1 l), V3 = (0.5 l) + (1 l) + (0.5 l), V4 = (0.67 l) + (0.67 l) + (0.67 l). Each treatment was repeated 3 times. The parameters observed were plant height, stem diameter, shoot dry weight and root dry weight, as well as the root shoot ratio. The result showed that the comparison of the planting media compositionÂ Â for ultisol, blotong and husk charcoal, in treatment V3 = (0.5 l) + (1 l) + (0.5 l) had a significant effect on plant height of 201.30 cm with an increase of 29.795%, stem diameter 21.77 mm with an increase of 38.92%, shoot dry weight 44.73 g with an increase of 158.55%, root dry weight 5.29 mm with an increase of 153.11%, root crown ratio 8.47 with an increase of 51.52 %.